ANALISIS PROBLEMATIKA PERKAWINAN BEDA AGAMA DI INDONESIA - Rahmatullah; Muh. Rifqy Ramadhan (Journal Publicuho, 2025)
This research discusses the problems of interfaith marriages in Indonesia., both in the form of religiously valid marriages and legally in the sense of being recognized by the State as well as the impact or implications of interfaith marriages in Indonesia. This research uses a type of Normative research by combining legal research methods that examine legal norms or rules (normative approach) by examining written rules, such as laws, regulations, or legal doctrines. The results of this study indicate that by the mandate of the marriage law article 2 paragraph (1) states that marriage is valid, if it is carried out according to the laws of each religion and belief, and is emphasized by paragraph (2) to obtain legality and administrative recognition. The implications of interfaith marriages for couples of different religions exist and are recognized administratively if the spouse files a lawsuit and the State Court in this case provides a recommendation for registration in the civil registry. However, this is recognized administratively but not religiously. The legal consequences arising from interfaith marriages are: 1) issues related to the validity of marriage or the nullity of marriage. 2) problems of inheritance specifically for Muslims. 3) problems in the event of a domestic case, because there are still legal issues within the authority of the court handling the case.